Simulation of high velocity inlet cyclone separator using computational fluid dynamic (CFD) approach - Ab Rahim, Nur Azira (2017)
This paper presents a computational fluid dynamics (CFD) simulation to evaluate the effect of velocity of inlet cyclone on the pressure drop of cyclone separator. The simulation of CFD code Fluent 6.1 is used to iterate the result. The CFD simulations predict excellently the cyclone pressure drop under different inlet velocity. The result shows that the pressure is decrease with the increase of velocity. Thus, the less power is needed to run the cyclone separator. Less power is more saving cost instead of high power consumption. Cyclone separator are commonly use to remove industrial dust from air under gas-solid separation. Cyclone is currently used in process industries like cement industries. Cyclone also being used as equipment to clean the gas in process of gasification, which consist of removal of dust particle in raw gas at fluidized and fixed bed gasifiers (Amit Kumar Singh Parihar). The number of type of cyclone is many but the common cyclone used is flow cyclone. Cyclone is less economical and have simple design. Cyclone is the type of device that use centrifugal force generated by spinning of gas. The magnitude is depends on particle mass, gas velocity within cyclone diameter. Due to its no moving parts, the cyclone separators considered as free maintenance.